The Pain–to–Well-Being Relationship in Patients Experiencing Chronic Orofacial Pain - Bhalang, Kanokporn; Steiger, Beat; Lukic, Nenad; Zumbrunn Wojczyńska, Aleksandra; Hovijitra, Ray S.; Ettlin, Dominik A. (Frontiers in Neurology, 2020)
Introduction: Orofacial pain features may negatively influence a person’s wellbeing and vice versa. Some aspects of wellbeing can be measured with axis II instruments that assess patients’ psychosocial and behavioral status. The aim of this study was to investigate associations between pain features and psychosocial variables as indicators of wellbeing. Materials and Methods: Seven hundred and ninety-nine anonymized datasets collected using the Web-based Interdisciplinary Symptom Evaluation (WISE) of patients reporting to the Interdisciplinary Orofacial Pain Unit, University of Zurich, between March 19, 2017 and May 19, 2019 were analyzed. Pain features including intensity, number of locations, impact, and duration were evaluated. Psychometric measures assessed pain-related catastrophizing and disability, illness perception, distress, anxiety, depression, injustice experience, dysmorphic concerns, and insomnia. Results: Most patients were between 30 and 59 years old (58.3%), female (69.8%), working (66.0%), and experienced pain for more than six months (68.5%). Pain intensities were higher in women than men and higher in disabled than working patients. Scores indicating elevated stress and depression were also observed in disabled patients. The sample prevalence of clinically relevant axis II instrument scores were: Graded Chronic Pain Scale for the Head (GCPS-H) 27%, Patient Health Questionnaire 4 (PHQ4) 21%, PHQ9 21%, Pain Catastrophizing Scale (PCS) 20%, General Anxiety Disorder 7 (GAD7) 15%, Insomnia Severity Index (ISI) 15%, Injustice Experience Questionnaire (IEQ) 14%, GCPS for the Body (GCPS-B) 13%, PHQ for Stress (PHQstr) 6%, and Dysmorphic Concern Questionnaire (DCQ) 2%. Noteworthy results of correlation analysis of the clinical relevant axis II scores and pain measures were as follows: the PHQstr had moderate associations (0.34‒0.43) with the sum of pain intensity at rest and during function, number of pain locations, and typical pain intensity. The IEQ scores were moderately associated with typical pain intensity at 0.39. The DCQ scores were moderately associated with pain extension at 0.41. Conclusions: Moderate correlations of certain pain and wellbeing measures were found in patients reporting clinically relevant stress, injustice experience and dysmorphic concern, all of which reflect impaired wellbeing. PHQ4 is suitable for routine distress screening in clinical setting.